Volleyball players` somatic composition in the light of sports results at 2014 FIVB Volleyball Men`s World Championship - Wnorowski, K.; Cieminski, K. (Baltic Journal of Health and Physical Activity, 2016)
Background: The aim of the study was to analyse sports results and the somatic composition of participants in the 2014 FIVB Volleyball Men's World Championship held in Poland.